Alterations in the gut microbiota of AIDS patients with pneumocystis pneumonia and correlations with the lung microbiota - Zhu, Mingli; Liu, Sai; Zhao, Chenfei; Shi, Jinchuan; Li, Chaodan; Ling, Shisheng; Cheng, Jianghao; Dong, Wenkun; Xu, Jiru (Frontiers in Cellular and Infection Microbiology, 2022)
Background This paper attempts to study the pathogenesis of PCP in AIDS patients from the microbiome perspectives, so as to provide better strategies for the diagnosis, treatment and prevention of PCP. Methods The subjects were divided into three groups: HIV infected patients combined with PCP group, HIV infected patients without PCP group and HIV negative group. Stool and bronchoalveolar lavage fluid (BALF) samples were collected. Total DNA of the samples were extracted. 16SrRNA high-throughput sequencing was performed in the Illumina MiSeq platform. PICRUSt and BugBase were used to predict the function of microflora. The correlation analysis of intestinal and lung bacterial flora was conducted also. Results Compared with HIV- group, prevotella and other 21 genera in the intestinal microbiome were statistically different in HIV+ group; 25 genera, such as Escherichia-Shigella, from group A were statistically different with group B. The abundance of Genera such as porphyromonas was positively or negatively correlated with CD16/CD56+ (μL) etc. respectively. Compared with HIV- group, for identification efficiency with AUC > 0.7 of HIV+ group, there were 7 genera including enterococcus (total AUC 0.9519) in gut microbiota. Compared with HIV+PCP- group, there were no bacteria with AUC > 0.7 in lung or intestine for HIV+PCP+. The number of the same bacteria between BALF and fecal were 8 species in HIV- group, 109 species in PCP- patients and 228 species in PCP+ patients, as seen in Venn diagram. The changes of various clinical indicators and blood parameters were also closely related to the increase or decrease of the abundance of intestinal and pulmonary bacteria respectively. Conclusions HIV infection and PCP significantly altered the species composition of lung and intestinal microbiome, HIV infection also significantly affected the gene function of intestinal microbiome, and PCP further promoted this change. The classification model can be used to distinguish HIV+ from HIV- patients, however, the efficiency of bacterial classification was poor between PCP+ and PCP- groups. The microbiome in the lung and gut showed a correlation to some extent, providing evidence for the existence of the lung-gut axis, and indicating a potential therapeutic target in patients with HIV and PCP.